Pristine dwarf galaxy survey – I. A detailed photometric and spectroscopic study of the very metal-poor Draco II satellite. Issue 2 (27th July 2018) - Longeard, Nicolas; Martin, Nicolas; Starkenburg, Else; Ibata, Rodrigo A; Collins, Michelle L M; Geha, Marla; Laevens, Benjamin P M; Rich, R Michael; Aguado, David S; Arentsen, Anke; Carlberg, Raymond G; Côté, Patrick; et al.
ABSTRACT: We present a detailed study of the faint Milky Way satellite Draco II (Dra II) from deep CFHT/MegaCam broad-band g and i photometry and narrow-band metallicity-sensitive CaHK observations, along with follow-up Keck II/DEIMOS multi-object spectroscopy. Forward modelling of the deep photometry allows us to refine the structural and photometric properties of Dra II: the distribution of stars in colour–magnitude space implies Dra II is old (13.5 ± 0.5 Gyr), very metal-poor, very faint ($L_V = 180 ^{+124}_{-72} {\rm \, L_\odot}$ ), and at a distance $d = 21.5 ± 0.4 {\rm \, kpc}$ . The narrow-band, metallicity-sensitive CaHK Pristine photometry confirms this very low metallicity ([Fe/H] = −2.7 ± 0.1 dex). Even though our study benefits from a doubling of the spectroscopic sample size compared to previous investigations, the velocity dispersion of the system is still only marginally resolved ($σ _{vr}\lt 5.9 {\rm \, km \, \, s^{-1}}$ at the 95 per cent confidence level) and confirms that Dra II is a dynamically cold stellar system with a large recessional velocity ($\langle v_{r}\rangle = -342.5^{+1.1}_{-1.2}{\rm \, km \, \, s^{-1}}$ ). We further show that the spectroscopically confirmed members of Dra II have a mean proper motion of $(μ _α ^*, μ _δ)=(1.26 ± 0.27, 0.94 ± 0.28) {\rm \, mas/yr}$ in the Gaia DR2 data, which translates to an orbit with a pericentre and an apocentre of $21.3 ^{+0.7}_{-1.0}$ and $153.8 ^{+56.7}_{-34.7} {\rm \, kpc}$, respectively. Taken altogether, these properties favour the scenario of Dra II being a potentially disrupting dwarf galaxy. The low-significance extra-tidal features we map around the satellite tentatively support this scenario.